The mediation role of academic achievement in the relationship between religiosity and pornography addictiveness among undergraduate students in Malaysia - Chan, Wei Hung; Lee, Jane; Lim, Zhen Chin (2022)
The cases of pornography addiction were increasing dramatically in Malaysia. Due to the conservative attitude of religion institution towards pornography usage, people with high religiosity may experience guiltiness when engaging in pornography viewing. It is also believed that academic achievement was positively predicted pornography addictiveness. Hence, this study is aimed to investigate the mediating effect of academic achievement between religiosity and pornography addictiveness. A quantitative research method and purposive sampling techniques were applied to recruit 120 undergraduate students from private and public universities of Malaysia. The questionnaire distributed consisted of three sections, which are demographic information (include CGPA), Centrality of Religiosity Scale (CRS) and Cyber Pornography Use Inventory-9 (CPUI-9). The single linear regression showed that religiosity can positively predict academic achievement. However, the result obtained from multi linear regression indicated there is no significant relationship between religiosity and pornography addictiveness. The relationship between academic achievement and pornography addictiveness was also not significant. The mediation analysis indicated academic achievement did not play a mediating role between religiosity and pornography addictiveness. The latest statistics obtained from this research able to fill in knowledge gap in mental health field. This research also contributes to the implementation of prevention program to create awareness towards pornography addiction issues and enhances psychological well-being.